A survey on the perception of in-service teachers toward cooperative learning in Universiti Malaysia Sarawak - Jien Michael, Ajap (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Cooperative Learning is a technique whereby students work together within a small group and through their interactions within the group; it can enhance the success of the learning process. This study aims to find out the in-service teachers' perception toward cooperative learning in Universiti Malaysia Sarawak (UNlMAS) in terms of their views, opinions and beliefs of cooperative learning. A total of 135 in-service teachers were selected from the education programmes namely, English as a Second Language, Science for Chemistry and Biology, and Information Technology. All the respondents are from 1St, 2nd, 3rd, and 4th year. Quantitative study design was employed and five-point likert scale questionnaire was administered. The results were categorized into three objectives namely, in-service teachers' perceptions toward cooperative learning, how do in-service teachers' benefits from cooperative learning and in-service teachers' participation in cooperative learning. Results from the questionnaire indicate that they feel free in expressing their opinions and ideas during group discussion, cooperative learning can enhance their social interaction, and they feel that the group works are divided equally among the group members.